2017
DOI: 10.1155/2017/1039161
|View full text |Cite
|
Sign up to set email alerts
|

Irisin: A Potential Link between Physical Exercise and Metabolism—An Observational Study in Differently Trained Subjects, from Elite Athletes to Sedentary People

Abstract: We compared irisin levels among groups of differently trained healthy individuals to explore the role of irisin as a physiological linker between exercise and metabolic health. Irisin and biochemical parameters of glucose and lipid metabolism were assessed in 70 healthy volunteers stratified for sport performance level into four groups: (1) 20 elite athletes of national level, (2) 20 subelite athletes of local level, (3) 20 recreational athletes, and (4) 10 sedentary subjects. All biochemical parameters were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 35 publications
4
40
0
1
Order By: Relevance
“…Blood samples were collected after an overnight fasting. Biochemical parameters (glucose, insulin, triglycerides, total and HDL-cholesterol, uric acid, creatinine, glycated hemoglobin (HbA1c), 25-hydroxy vitamin D (25OHD) and non-esterified free fatty acids (NEFA)) were assayed using Cobas 6000 analyzer (Roche Diagnostics, Milan, Italy) as previously reported [5,24,25]. LDL-cholesterol was calculated with the Friedewald's formula.…”
Section: Blood Collection and Biochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were collected after an overnight fasting. Biochemical parameters (glucose, insulin, triglycerides, total and HDL-cholesterol, uric acid, creatinine, glycated hemoglobin (HbA1c), 25-hydroxy vitamin D (25OHD) and non-esterified free fatty acids (NEFA)) were assayed using Cobas 6000 analyzer (Roche Diagnostics, Milan, Italy) as previously reported [5,24,25]. LDL-cholesterol was calculated with the Friedewald's formula.…”
Section: Blood Collection and Biochemical Parametersmentioning
confidence: 99%
“…Irisin has also been shown to have important metabolic functions. In particular, it can decrease glucose level, improve insulin resistance [3][4][5][6][7] and, interestingly, counteract some detrimental effects induced by advanced glycation end products (AGE) [8]. By binding to RAGE (membrane receptor for AGE), AGE may in fact promote inflammation, oxidative stress and endothelial dysfunction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies on the impact of exercises on the recently-discovered irisin are limited and the publications that express that only the acutely performed resistance and aerobic exercises increase the irisin concentration [16,17,18], but the long-term exercise programs do not affect the irisin concentration [19,20,21], and recent studies even reduce irisin [22] are encountered as well. It appears that the studies regarding the responses of irisin to acute and chronic exercises have been conducted in different age groups and in the study design with different exercise type and duration (resistance, aerobic etc), in the healthy females and males with different activity levels [23,24,25], in the patients with diabetes [26] or in obese individuals [27]. It was observed that even though the impacts of training and gender have been researched in the studies about irisin, the subjects were not elite athlete.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies conducted after the discovery of irisin revealed controversial results in terms of circulating levels of irisin, especially after exercise The studies reported that acute or chronic exercise has an important effect on the increase of the irisin levels [9,10]. In addition, there are studies that exercise has no impact on the irisin level [11,12] or has reductive impacts on it [13,14].…”
Section: Introductionmentioning
confidence: 99%